CONVERGENCE STRATEGY OF LIVESTOCK PRODUCTION AND ANIMAL BIOMODELS FOR HUMAN WELLNESS IN FUTURE: A REVIEW - SO PARK (Journal of Animal and Plant Sciences, 2024)
As human lifespan increase, interest in human health is also increasing. Therefore, it is necessary to converge livestock production and animal biomodels. In the fourth industrial revolution, animal biomodels as algorithms in agriculture are emerging rapid evolution by converging enovation technologies in fields of bio-healthcare, biomedical research, and life science. Animal biomodels have been used as important foundational tools to transit screening processes and clinical trials for useful substances and potential drugs in human and animal life science. Animal biomodels for studying human and animal diseases have enabled medical innovation and derived numerous outcomes such as vaccines. It is very important to choose appropriate animal biomodels in clinical studies. When selecting experimental animals for human and animal diseases, some parameters should be kept in mind. Convergence of livestock production with animal biomodel can help us greatly solve human and animal health diseases and welfare issues. It enables prevention of human diseases and vaccine development for emerging infectious diseases by applying appropriate animal biomodels, thus contributing to the development of bio-healthcare industry. Animal biomodels are in vivo models for determining mechanisms of life phenomena and diseases progression. They can also be used to evaluate the safety, effectiveness, new cosmetic materials, and action mechanisms of functional materials and foods. Animal experiments using animal biomodels must be based on ethical considerations. Animal biomodels can be produced through drugs, diet, surgical procedures, spontaneous mutation, crossbreeding, biotechnology such as transformation and genetic manipulation, and so on. In this paper, preemptive response strategies for the development of livestock and biomedical industry of the future are reviewed through understanding the importance of animal biomodels as animal life science algorithms. Animal models for studying mechanisms of diseases in human, livestock, and birds, in ovo technology for poultry, preparation theories, animal bioethics, and practical cases are also explained.
Keywords: Bio-healthcare; biomedical; life science; clinical trial; animal bioehtics